2018
DOI: 10.1002/oby.22244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal BMI on Rubella Nonimmunity at Antenatal Screening

Abstract: High maternal BMI (≥ 25.0 kg/m ) is associated with reduced rubella immunity, an effect confined to gravidas with almost complete vaccine coverage in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Obesity can impair the regulation of immune responses by promoting lipid deposition in lymphoid tissues, alterations in leukocyte profiles and activity, and chronic inflammation. While studies have previously demonstrated that obesity negatively impacts the efficacy of vaccines against influenza, hepatitis B, and tetanus (), the current work of Hui et al () is novel in that it is one of few studies to find an association between high BMI and immunity against rubella, and the first study to identify this trend in pregnant women—a population most at risk for conferring severe effects of rubella infection to offspring.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Obesity can impair the regulation of immune responses by promoting lipid deposition in lymphoid tissues, alterations in leukocyte profiles and activity, and chronic inflammation. While studies have previously demonstrated that obesity negatively impacts the efficacy of vaccines against influenza, hepatitis B, and tetanus (), the current work of Hui et al () is novel in that it is one of few studies to find an association between high BMI and immunity against rubella, and the first study to identify this trend in pregnant women—a population most at risk for conferring severe effects of rubella infection to offspring.…”
mentioning
confidence: 92%
“…While various factors have been associated with declining rubella immunity following childhood immunization, Hui et al () present compelling evidence to suggest that elevated body mass index (BMI) may impair serological immunity against rubella in pregnant women. In this large‐scale retrospective cohort study, pregnant women with BMI > 25.0 kg/m 2 were more likely to present with serological rubella nonimmunity (rubella IgG antibody titer < 10 IU/ml), as compared to women with BMI < 25.0 kg/m 2 .…”
mentioning
confidence: 99%